Gender Specific Study on Relative Impact of Convenience and Non Convenience Factors on Mobile Users’ Brand Switching in Kolkata - Biswas, Supriya (Indian Journal of Marketing, 2012)
Switching behavior, irrespective of the product and services is not uncommon in the present-day context, where loyalty has become uncertain. While the same applies in case of mobile users, causes could be varied and many of those have already been identified that contribute to such an act. What is not clearly explored is the gender-specific profile of this switching behavior in case of mobile users. Research focusing on business-to-business relationships is likely to be male dominated and deal with male-male relationships. As such, it may not apply equally to other types of relationships (female-male or female-female). Similarly, most research in consumer relationship marketing is based on theoretical frameworks developed in western cultures. It is quite possible that the benefits received, or their importance, in firm-consumer relationships may be very different when considered in other cultural contexts. This paper fills a gap in the current thinking about how to identify the consumers who engage themselves in relational behavior by considering these missing links, particularly while viewed in the Indian context and subsequent identification of the key factors that drive the switching behavior. The study has been conducted with the following objective in focus, namely, identification of relative importance of key factors (convenience and other than convenience, i.e., Price, Service Provider’s Indifference & nothing specific (clubbed together as ’Other than Convenience’) influencing the consumers into the act of switching the service provider, exploring how the switching behavior varies between the genders. The study was conducted during June-July 2010.